Stimulating epistemological curiosity through investigative activities in Geometry with educational robotics - Gabrielly Cristina Souza Ferreira; Rejane Waiandt Schuwartz de Carvalho Faria (Educação Matemática Debate)
This article aims to discuss the stimulation of Epistemological Curiosity through Investigative Activities in Geometry with Educational Robotics in Middle School. The work is theoretically based on Mathematical Investigations and address students' curiosity in the relationship between Geometry, Digital Technologies and Educational Robotics. In the study carried out, we opted for qualitative research methodology, as it prioritizes data collection in a personal and interpretative way. The research results reveal that Educational Robotics, when incorporated as a pedagogical tool, provided students with a rich and innovative experience, distinct from traditional approaches, developing geometric knowledge through meaningful learning and contributing to the development of epistemological curiosity.